Politeness Maxim in Real Time with Bill Maher Shows with Elon Musk - Pebriyana Kosasih; Nurindah Putri Sunitha; Muhamad Afri Arya Dilla; Dwi Rahayu (Proceedings Series on Social Sciences & Humanities, 2024)
The goal of this study is to examine the politeness maxims that appeared in Real Time with Bill Maher talk show program. The research of this study used qualitative descriptive methods. The researchers applied Geofrrey Leech's (1983) theory of politeness maxims to analyze the data. Leech presented six different types of politeness maxims: the Tact Maxim, the Generosity Maxim, the Modesty Maxim, the Approbation Maxim, the Agreement Maxim, and the Sympathy Maxim. The conversation between William Maher and Elon Musk provided the data for this study. The study's findings indicate that the presenters of these shows used twenty eight politeness maxims. The presenter uses a variety of politeness maxims, including: seven tact, four generosity, four approbation, four modesty, four agreement, and five sympathy. The tact maxim and sympathy maxim are the ones Maher uses the most, while the tact maxim and modesty maxim are the ones Musk uses the most. It can be concluded that In the Real Time with Bill Maher talk show program, people who have close relationships minimize harm to others and maximize their benefits, especially to their loved ones.